Root Biology Growth, Physiology, and Functions - Ohyama, Takuji (IntechOpen, 2019)
This book provides up-to-date knowledge of root biology. Most plants have roots, which anchor the plant in the soil and physically support the above-ground parts of the plant. In addition, roots absorb water and nutrients from the soil and transport this to the shoot. Roots grow by cell proliferation in the meristem in the root tip. The cells differentiate into the epidermis, cortex, and stele. Water and nutrients are absorbed through the cell membrane of the epidermis and are transported to the above-ground parts via xylem vessels. The root growth and functions are affected by various abiotic and biotic conditions, such as levels of water, salt, acid stresses, and presence of soil diseases. However, some beneficial microorganisms such as rhizobia and mycorrhizal fungi help plant growth.